Dampak Penerapan Green Accounting, Kinerja Lingkungan dan Biaya Modal Terhadap Kinerja Keuangan Pada Perusahaan Energi Tahun 2021-2024 - Nur Miftakhul Ilmi; Shafrani Dizar (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Global climate change and environmental damage caused by energy sector activities have created an urgent need to implement a green accounting approach and effectively manage environmental costs. The purpose of this study is to analyze the influence of green accounting practices, environmental performance, and the cost of capital on the financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This study used a quantitative method with a simple linear regression analysis approach on company financial report data. The results show that green accounting practices have a negative impact on financial performance in the short term. This is due to increased environmental investment costs, which reduce company profits at the initial implementation stage. However, these practices can still drive long-term net profit growth by creating efficiencies and a positive reputation that support company competitiveness. Furthermore, good environmental performance tends to lead to increased expenditures to meet environmental standards and regulations, such as certification costs or environmentally friendly technology. While this negatively impacts short-term financial performance, long-term benefits such as reduced environmental risks and increased investor confidence can be achieved. Furthermore, an efficient cost of capital has been shown to positively impact financial performance. Companies that are able to manage their capital structure well are better able to fund operational activities and environmental investments without significantly burdening the balance sheet. This research emphasizes the importance of an integrated strategy between economic and environmental sustainability goals. Therefore, companies need to design efficient green accounting policies, strategically manage environmental costs, and optimize capital structure. Recommendations for further research include expanding the scope of variables, industrial sectors, and extending the observation period to obtain a more comprehensive picture.